Optimization of single and mixed cultures for solid state fermentation of municipal sewage sludge - Kabbashi, Nassereldeen Ahmed; Ramachandran, K.B; Fakhru’l-Razi, Ahmadun; Muyibi, Suleyman Aremu (Taylor & Francis Group Ltd, 2005)
Trichoderma harzianum (Th), Phanerochaete chrysosporium ATCC 24725 (Pc) and Mucor hiemalis (Mh) isolated from three sources: wastewater; sewage sludge; and sludge cake were selected for use as compatible/incompatible single and mixed cultures in the treatment of munici- pal sewage sludge. Five experiments were carried out using (Pc), (Th), a mixture of (Pc/Th), (Mh) and a mixture of (Pc/Mh), in addition to a control where no micro-organism was used. The experiments were used to evaluate their potential performance as compatible/incompatible single and mixed cultures for the treatment of municipal wastewater sewage sludge from treatment plants using solid state fermentation technique (SSF). The results showed that the best micro- organism for composting was found to be (Th) and a mixture of (Pc/Th), while (Pc/Mh) was incompatible culture. The C/N ratio for Th changed from 8.46 to 17.8 at the end of the process, (Ph/Th) increased from 7.21 to 15.9, while (Pc/Mh) increased from 8.49 to 29. The pH value also affected by the fungal cultures which was also changed for (Th) from 4.29 to 6.8, for (Pc/Th) was changed from 7.27 to 6.7 and for (Pc/Mh) was changed from 6.6 to 5.3. Effective results were observed by using mixed culture after 19–21 days compared to other single treatments after 24–32 days.